Nonspecific Effects of Normal Aging on Taxonomic and Thematic Semantic Processing. Issue 1 (1st January 2023) - Merck, Catherine; Noël, Audrey; Jamet, Eric; Robert, Maxime; Salmon, Anne; Belliard, Serge; Kalénine, Solène
ABSTRACT: Objective: This study aimed to assess the effect of normal aging on the processing of taxonomic and thematic semantic relations. Method: We used the Visual-World-Paradigm coupled with eye-movement recording. We compared performance of healthy younger and older adults on a word-to-picture matching task in which participants had to identify each target among semantically related (taxonomic or thematic) and unrelated distractors. Results: Younger and older participants exhibited similar patterns of gaze fixations in the two semantic conditions. The effect of aging took the form of an overall reduction in sensitivity to semantic competitors, with no difference between the taxonomic and thematic conditions. Moreover, comparison of the proportions of fixations between the younger and older participants indicated that targets were identified equally quickly in both age groups. This was not the case when mouse-click reaction times were analyzed. Conclusions: Findings argue in favor of nonspecific effects of normal aging on semantic processing that similarly affect taxonomic and thematic processing. There are important clinical implications, as pathological aging has been repeatedly shown to selectively affect either taxonomic or thematic relations. Measuring eye-movements in a semantic task is also an interesting approach in the elderly, as these seem to be less impacted by aging than other motor responses.